Structural and magnetic properties of Co-doped Er2O3 nanoparticles - (:unkn) unknown (ELSEVIER, 2015)
Er-2_xCoxO3 (x=0.00, 0.04, 0.10, 0.30, 0.4) solutions were synthesized by the sol-gel technique using erbium 2,4 pentadionate and cobalt acetylacetonate dissolved in methanol and acetyl acetone. The various obtained Co-doped Er2O3 nanoparticles were annealed at 900 degrees C to hod a doping effect on the structural and magnetic properties. The crystal structures and morphology of the Co-doped Er2O3 nanoparticles were characterized using 2 theta-theta X-ray diffraction (XRD) and scanning electron microscope (SEM). ESR spectra of Er-2_xCoxO3 nanoparticles were collected at room temperature with a Bruker EMX model X-band spectrometer at a frequency of 9.5 GHz. (C) 2014 Elsevier By. All rights reserved.
Keywords: Nanoparticle; Magnetic property; Co doped Er2O3; Sol-gel; COATED CONDUCTOR DEVELOPMENT; X-RAY-DIFFRACTION; SOL-GEL; THIN-FILMS; OPTICAL-PROPERTIES; TEMPERATURE; MICROSTRUCTURE; POWDER